Association Between Vascular Index Measured via Superb Microvascular Imaging and Molecular Subtype of Breast Cancer - Zhang, Xiao-Yan; Cai, Si-Man; Zhang, Li; Zhu, Qing-Li; Sun, Qiang; Jiang, Yu-Xin; Wang, Hong-Yan; Li, Jian-Chu (Frontiers in Oncology, 2022)
Abstract Background: To determine whether vascular index (VI, deﬁned as the ratio of Doppler signal pixels to pixels in the total lesion) measured via superb microvascular imaging in breast cancer correlates with immunohistochemically defined subtype and is able to predict molecular subtypes. Methods: This prospective study involved 225 patients with 225 mass-type invasive breast cancers (mean size 2.6±1.4cm, range 0.4~5.9cm) who underwent ultrasound and superb microvascular imaging (SMI) at Peking Union Medical College Hospital before breast surgery from December 2016 to June 2018. The correlations between primary tumor vascular index（VI）measured via SMI, clinicopathological findings and molecular subtype were analyzed. The performance of VI for prediction of molecular subtypes in invasive breast cancer was investigated. Results: The median VI of the 225 tumors was 7.3% (4.2%~11.8%) (Range 0~54.4%). Among the subtypes of the 225 tumors, 41(18.2%) were luminal A, 91(40.4%) were luminal B (HER-2 -negative), 26 (11.6%) were luminal B (HER-2 -positive), 17 (7.6 %) were HER-2 -positive and 50 (22.2 %) were triple-negative, and the corresponding median VI were 5.9% (2.6%~11.6%) (Range 0~47.1%), 7.3 (4.4%~10.5%) (Range 0~29.5%), 6.3% (3.9%~11.3%) (Range 0.6%~22.2%), 8.2% (4.9%~15.6%) (Range 0.9%~54.4%) and 9.2% (5.1%~15.3%) (Range 0.7%~32.9%), respectively. ER negative, higher tumor grade and higher Ki-67 index (≥20%) was significantly associated with a higher VI value. Tumor size, ER status, Ki-67 index were shown to independently influence VI. A cut-off value of 4.1% yielded 79.9% sensitivity and 41.5% specificity with an area under the receiver operating characteristics curve (AUC) of 0.58 for predicting that a tumor was of the luminal A subtype. A cut-off value of 16.4% yielded 30.0% sensitivity and 90.3% specificity with an AUC of 0.60 for predicting a triple-negative subtype Conclusions: VI, as a quantitative index obtained by SMI examination, could reflect histologic vascular changes in invasive breast cancer and was found to be higher in more biologically aggressive breast tumors. VI shows a certain degree of correlation with the molecular subtype of invasive breast cancer, and plays a limited role in predicting the luminal A with high sensitivity and triple-negative subtype with high specificity.